Critical behavior of the ferromagnetic transition in GdSc(Si, Ge) intermetallic compounds. (October 2018) - Herrero, A.; Oleaga, A.; Manfrinetti, P.; Provino, A.; Salazar, A.
Abstract: A complete study on the critical behavior of the paramagnetic to ferromagnetic transition in intermetallics GdScSi, GdScGe, GdSc(Si0.5 Ge0.5 ) and Gd(Sc0.5 Ti0.5 )Ge has been carried out by means of magnetic as well as calorimetric measurements, using a high resolution ac photopyroelectric technique. The critical exponents α, β, γ, δ and the ratio of the critical coefficients A + /A − have been independently obtained for the four samples. It has been proved that the magnetic interactions are short range as the values of the critical parameters correspond to the 3D-Heisenberg class, stating an isotropic ordering of the Gd spins. In some cases, there are small deviations of some of the critical parameters from the theoretical values which have been discussed on the basis of the variation of the d states hybridization between the rare earth and the transition metal, as well as the presence of small magnetocrystalline anisotropies arising from spin-orbit coupling effects. Highlights: Critical behavior of GdScSi, GdScGe, GdSc(Si0.5 Ge0.5 ), Gd(Sc0.5 Ti0.5 )Ge is studied. α, β, γ, δ, A + /A − have been independently obtained using 5 methods. 3D-Heisenberg model agrees with all of them: isotropic magnetism. Small deviations for γ, A + /A − from the theoretical values in some cases. Different orbital hybridization and spin-orbit coupling responsible for the deviations.